Morphology of the glymphatic and meningeal lymphatic structures of the bottlenose dolphin - Tiffany F. Keenan; Olivia N. Jackson; Nathan P. Nelson-Maney; Sentiel A. Rommel; William A. McLellan; D. Ann Pabst; Alexander M. Costidis; Kathleen M. Caron; Dawn N. Kernagis; David S. Rotstein; Molly Braun; Michael S. Tift (Scientific Reports)
Abstract In humans and mice, the glymphatic system, critical for central nervous system (CNS) health, relies on cardiorespiratory coupling, but has not yet been investigated in a diving mammal that routinely experiences apnea, bradycardia, and peripheral vasoconstriction. The glymphatic and meningeal lymphatic systems maintain CNS homeostasis by distributing nutrients and clearing metabolic waste via cerebrospinal fluid. We investigated meningeal lymphatic and glymphatic structures in stranded bottlenose dolphins (Tursiops truncatus; n = 9) using immunofluorescence microscopy, histochemical staining, and CT angiography. Results demonstrate that the bottlenose dolphin possesses prominent perivascular spaces and aquaporin-4 astroglial water channels required for glymphatic function, as well as meningeal lymphatic vessels in close anatomic proximity to dural venous sinuses, required for a functional meningeal lymphatic system. Notably, we also identified arachnoid granulations involved in cerebrospinal fluid resorption, marking the first such observation in this species. This study provides evidence of both glymphatic and meningeal lymphatic systems in the most well-studied cetacean, the bottlenose dolphin.